Optimal scheduling of hypofractionated radiotherapy for localized prostate cancer: A systematic review and metanalysis of randomized clinical trials. (November 2018) - Arcangeli, Giorgio; Arcangeli, Stefano; Pinzi, Valentina; Benassi, Michaela; Benassi, Marcello; Strigari, Lidia
Highlights: Non-inferiority phase III trials support hypofractionated RT for localized prostate cancer. No hypofractionated regimen of RT for prostate cancer has proven to be superior to others. We searched the hypofractionated schedules of RT associated to the best therapeutic ratio. We found a range within which total dose, daily fraction and number of fractions can be safely adjusted. The extrapolation to extremely hypofractionated RT regimens is not warranted. Abstract: Purpose: We sought to determine the optimal hypofractionated regimens of moderately hypofractionated (HFRT) versus conventionally fractionated (CFRT) external beam radiotherapy for localized prostate cancer (LPCA), having as primary endpoints the 5-year biochemical failure (BF) and late gastrointestinal (GI) and genitourinary (GU) toxicity. Methods and materials: We performed a systematic literature review of the Medline and National Library of Medicine databases according to the PRISMA guidelines. Only phase III trials of CFRT versus moderate HFRT for LPCa, reporting 5-year BF and/or minimum 3-year late ≥G2 toxicity rates were considered. Results: A total of 11 manuscripts reporting the outcomes of 8145 patients gathered from 9 randomized trials met the eligibility criteria. No significant difference between CFRT and HFRT was found in any of the investigated outcome measures. 80%, 15% and 29% isolevel curves for freedom from BF (FFBF), GI and GU toxicity, respectively, resulting from grouping the median values of all endpoints, were calculated as a function of both total dose ( Dtot ) and dose per fraction ( d ). Trials using fractionation schedules ( d  ×  n ) lying above the FFBF and below toxicity isolevels are expected to produce the best therapeutic ratio. Conclusions: Our analysis indicates an optimal therapeutic window within which Dtot, d and n can be safely adjusted. Owing to both the risks of uncertainty due to inclusion of trials with d up to 3.5 Gy, and the exploitation of different cell killing mechanisms associated to larger d, the extrapolation to extremely hypo-fractionated regimens is not warranted.